2021
DOI: 10.1039/d0ra09550h
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free high-adsorption-capacity adsorbent derived from spent coffee grounds for methylene blue

Abstract: Spent coffee grounds derived carbon was prepared for the adsorption of methylene blue in aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Multiple mechanisms could explain the decreasing adsorption of soluble Fe with higher SCGs addition. The adsorption times used in this study are higher than in previous SCGs adsorption studies (Lavecchia et al 2016;Nam et al 2017;Sukhbaatar et al 2021), which could cause desorption. However, Kyzas et al (2012) reports the adsorption of soluble metals onto SCGs under experimental adsorption times up to 24 h, which do not indicate desorption of soluble metals from the SCGs.…”
Section: Adsorptionmentioning
confidence: 76%
“…Multiple mechanisms could explain the decreasing adsorption of soluble Fe with higher SCGs addition. The adsorption times used in this study are higher than in previous SCGs adsorption studies (Lavecchia et al 2016;Nam et al 2017;Sukhbaatar et al 2021), which could cause desorption. However, Kyzas et al (2012) reports the adsorption of soluble metals onto SCGs under experimental adsorption times up to 24 h, which do not indicate desorption of soluble metals from the SCGs.…”
Section: Adsorptionmentioning
confidence: 76%
“…It was observed that the adsorption capacity increased with pH such that maximum absorbance quotient was obtained at pH 10 due to enhanced electrostatic interactions between MB molecules and oxygencontaining functional groups on the adsorbent surface introduced by KOH-NaOH activation. 260 Biomass/waste-derived porous carbons have also been explored for mixed dyes removal from wastewater. Wu et al reported high adsorption capacity of two kinds of organic dyes, congo red (404.4 mg g À1 ) (CR) and MG (2468 mg g À1 ) on activated porous carbon derived from HTC processed litchi peel.…”
Section: Environmental Remediationmentioning
confidence: 99%
“…It was observed that the adsorption capacity increased with pH such that maximum absorbance quotient was obtained at pH 10 due to enhanced electrostatic interactions between MB molecules and oxygen-containing functional groups on the adsorbent surface introduced by KOH–NaOH activation. 260…”
Section: Applications Of Nanoporous Carbonsmentioning
confidence: 99%
“…Many researchers have explored the adsorption capacity of biowaste coffee grounds for potential applications in wastewater remediation [13][14][15][16]. Lots of food waste that find its way into municipal sewage can pose major environmental risks to public health.…”
Section: Introductionmentioning
confidence: 99%